Hepatitis C virus NS3 protease genotyping and drug concentration determination during triple therapy with telaprevir or boceprevir for chronic infection with genotype 1 viruses, southeastern France. Issue 11 (23rd July 2014) - Aherfi, Sarah; Solas, Caroline; Motte, Anne; Moreau, Jacques; Borentain, Patrick; Mokhtari, Saadia; Botta‐Fridlund, Danielle; Dhiver, Catherine; Portal, Isabelle; Ruiz, Jean‐Marie; Ravaux, Isabelle; Bregigeon, Sylvie; et al.
Abstract Telaprevir and boceprevir, the two first hepatitis C virus (HCV) NS3 protease inhibitors (PIs), considerably increase rates of sustained virologic response in association with pegylated interferon and ribavirin in chronic HCV genotype 1 infections. The 30 first patients treated by telaprevir or boceprevir including anti‐HCV therapies since 2011 in Marseille University hospitals, France, were monitored. HCV loads and plasmatic concentrations of telaprevir and boceprevir were determined on sequential blood samples. HCV NS3 protease gene population sequencing was performed at baseline of treatment and in case of treatment failure. Fifteen patients (including 7 co‐infected with HIV) received telaprevir and the other 15 patients (including 4 co‐infected with HIV) received boceprevir. At baseline, HCV NS3 protease from six patients harbored amino acid substitutions associated with PI‐resistance. Treatment failure occurred at week 12 for 7 patients. Amino acid substitutions associated with PI‐resistance were observed in six of these cases. HCV NS3 R155K and T54A/S mutants, all of genotype 1a, were found from four patients. Median (interquartile range) plasma concentrations were 3, 092 ng/ml (2, 320–3, 525) for telaprevir and 486 ng/ml (265–619) for boceprevir. For HIV–HCV co‐infected patients, median concentrations were 3, 162 ng/ml (2, 270–4, 232) for telaprevir and 374 ng/ml (229–519) for boceprevir. Plasma drug concentration monitoring revealed undetectable concentrations for two patients at week 4, and probable non‐adherence to therapy for another patient. These findings indicate that routine HCV NS3 protease sequencing and plasma PI concentration monitoring might be helpful to characterize cases of therapy failure, at a cost dramatically low compared to that of anti‐HCV therapy. J. Med. Virol. 86:1868–1876, 2014. © 2014 Wiley Periodicals, Inc.